Pengaruh E-Commerce, Tarif Pajak Terhadap Penggelapan Pajak: E-COMMERCE DAN TARIF PAJAK - Wardani, Dewi Kusuma; Rahayu, Puji (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to examine the effect of E-commerce and Tax Rates on Tax Evasion. The data used are primary data. The method used is multiple regression analysis. The sampling technique used in this study was convinence sampling and 102 data samples. Regression test results show that tax rates affect tax evasion, while E-commerce do not affect tax evasion. Keywords: E-commerce and Tax Rates